Molecular Insight Into Key Eco-Physiological Process in Bioremediating and Plant-Growth-Promoting Bacteria - Mandal, Subhrangshu; Saha, Kunal Kumar; Mandal, Narayan Chandra (Frontiers in Agronomy, 2021)
Over the past few decades, the massive increase in anthropogenic activity and industrialization processes has increased new pollutants in the environment. The effects of such toxic components (heavy metals, pesticides, etc.) in our ecosystem vary significantly and are of significant public health and economic concern. Because of this, environmental consciousness is increasing amongst consumers and industrialists, and legal constraints on emissions are becoming progressively stricter; for the ultimate aim is to achieve cost-effective emission control. Fortunately, certain taxonomically and phylogenetically diverse microorganisms (e.g., sulfur oxidizing/reducing bacteria) are endowed with the capability to remediate such undesired components from diverse habitats and have diverse plant-growth-promoting abilities (auxin and siderophore production, phosphate solubilization, etc.). However, the quirk of fate for pollutant and plant-growth-promoting microbiome research is that, even with an early start, genetic knowledge on these systems is still considered to be in its infancy due to the unavailability of in-depth functional genomics and population dynamics data from various ecosystems. This knowledge gap can be breached if we have adequate information concerning their genetic make-up, so that we can use them in a targeted manner or with considerable operational flexibility in the agricultural sector. Amended understanding regarding the genetic basis of potential microbes involved in such processes has led to the establishment of novel or advanced bioremediation technologies (such as the detoxification efficiency of heavy metals), which will further our understanding of the genomic/genetic landscape in these potential organisms. Our review aimed to unravel the hidden genomic basis and eco-physiological properties of such potent bacteria and their interaction with plants from various ecosystems.